Toxic Effects Of Non-Steroidal Anti-Inflammatory Drugs Piroxicam And Mefenamic Acid And Their Roles As Cancer Chemopreventive Agents - Sanat, Faizah (2004)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the most widely used drugs worldwide. More NSAIDs were being produced and manufactured everyday. It was an overwhelming view that the thought of all NSAIDs were important due to their therapeutic actions by inhibiting the production of prostaglandin was challenged by the discovery that they affect a wide variety of cellular processes along the way. The NSAIDs piroxicam and mefenamic acid have dissimilar chemical structures, enolic and carboxylic acid respectively, but with the same mode of action for therapeutic uses. They both inhibit prostaglandin synthesis by inhibiting the cyc100xygenase (COX) pathway as of other conventional NSAIDs. However in some cases, they did differ with each other depending on the gravity of their effects on certain aspects. Although the toxicity of piroxicam was well known and documented, mefenamic acid is still not the safest drugs of all. Histologically, mefenamic acid showed a marked toxicity to the liver and kidney of rats compared to piroxicam. Morphological changes